Shorter maybe better: Psychometric properties of the UWES-3 items for measuring engagement in university Mexican teachers - Juárez García, Arturo (2023)
Introduction: Work engagement is a relevant positive psychological effect in the literature, and validity studies of the ultra-brief version of the Utrecht Work Engagement Scale are practically nonexistent in Latin America. Objective: to identify the psychometric properties of the ultra-brief version of the Utrecht Work Engagement Scale (UWES-3) and to analyze its equivalence with the UWES-9 version in a sample of teachers from a public university in Mexico. Method: the final sample consisted of N=247 university teachers, who answered the 9-item and 3-item versions of the UWES and the Burnout Evaluation Questionnaire for Education Personnel (CESQT-PE) to estimate its discriminant validity. Results: The results confirmed very high correlations between both versions of the UWES (3-9) (r=>.82-.93), a unidimensional structure of the UWES- 3 with higher factor loadings (>.75), satisfactory internal consistency values (>.70) and high and similar correlations in the expected direction between both versions and the CESQT-PE (q=.02-.08). Conclusions: We conclude that there is equivalence of the UWES-3 and the UWES-9. The practical benefits of the ultra-brief version for the measurement of work engagement in university teachers are discussed.